ANALISIS KINERJA SIMPANG EMPAT TAK BERSINYAL KOTA WETAN KABUPATEN GARUT METODE PKJI 2023 DAN SOFTWARE VISSIM - Solehudin, Rifqi; Saepudin, Uu; Martha, Taufik (Jurnal Ilmiah Teknik Sipil, 2026)
Intersections in Garut Regency, particularly the Kota Wetan Garut intersection connecting Ahmad Yani Road, Guntur Road, and Gagak Lumayung Road, often experience congestion during rush hour due to the lack of traffic control (APILL) and on-street parking. This study aims to analyze the performance of unsignalized intersections located in Kota Wetan, Garut Regency, based on traffic volume, intersection capacity, degree of saturation, delays, and level of service (LOS) parameters using the Pedoman Kapasitas Jalan Indonesia (PKJI 2023) and VISSIM software. The analysis results show a traffic volume of 1,559 smp/hour with a capacity of 4,350 smp/hour, a degree of saturation (DS) of 0.36, and an intersection delay of 8.82 seconds/smp, categorized as level of service B (Good) according to the 2023 PKJI. The VISSIM simulation results show a queue length of 12.96 m, an intersection delay of 13.95 seconds/smp, and an intersection level of service (LOS) of level B (Good). The intersection delay value based on PKJI 2023 was 8.82 seconds/smp, while the VISSIM software was 13.95 seconds/smp. Therefore, the intersection service level according to the Intersection Service Level Table Based on Delay is both at level B (Good), indicating that the condition is still relatively good, so no corrective action is needed.